Hubungan Manajemen Pelaksanaan Pemantauan Pertumbuhan Terhadap Partisipasi Masyarakat Dalam Kegiatan Posyandu Di Dusun 03 Desa Manislor - Nadia Aimatun Nisa; Popy Viranti; Donasyhafira Bella Sayekti; Indra Surya Permana (LPPM ITEKES Mahardika, 2021)
Posyandu is a form of Community-Based Health Efforts (UKBM) which is managed and organized from, by, for and with the community in carrying out community health development, community empowerment and providing convenience for the community in obtaining basic health services to accelerate the reduction of maternal and infant mortality. (Ministry of Health, 2011). In general, this study aims to determine the relationship between management and implementation of growth and development monitoring on the achievement of the presence of mothers and children under five at the Posyandu Dusun 03 Manislor Village, Jalaksana District. The method used in collecting data in this research is a qualitative method. Posyandu Dusun 03 Manislor Village, community participation in participating in posyandu activities is quite good, because the number of visits every month reaches 70.5% - 88.2% although it often goes up and down, but the number of visits by mothers and toddlers to posyandu has never been <50%. Growth monitoring management in terms of the management system as described includes elements (Input, Process, Output) and includes 6M elements (Man, Money, Material, Machine, Method, Market). The lack of participation of mothers in posyandu can result in low monitoring of growth and development in toddlers and is closely related to the facilities and infrastructure available for growth monitoring activities.